A heat transfer and friction factor correlation for low air-side Reynolds number applications of compact heat exchangers (1535-RP). (2nd January 2017) - Shinde, Pradeep; Lin, Cheng-Xian
Abstract : In this article, an experimental investigation of the heat transfer and pressure drop of compact heat exchangers with louvered fins and flat tubes was conducted within a low air-side Reynolds number range of 20< ReLp < 200. Using an existing low-speed wind tunnel, 26 sample heat exchangers of corrugated louver fin type, were tested. New correlations for Colburn factor j and Fanning friction factor f have been developed using eight nondimensional parameters based on the experimental data. Within the investigated parameter ranges, it seems that both the j and f factors are better represented by two correlations in two flow regimes (one for ReLp = 20 – 80 and one for ReLp = 80 – 200) than single regime correlation in the format of power-law. The results support the conclusion that airflow and heat transfer at very low Reynolds numbers behaves differently from that at higher Reynolds numbers.